Long-term bisphosphonate use and femoral morphological changes in osteoporosis patients: a retrospective cohort study - Junxiong Zhu; Chengchun Shen; Robert McCulloch; Danhua Ling; Kai Xu; Lidong Wu; Jiapeng Bao; Gun-Woo Lee; Lifeng Jiang (European Journal of Medical Research)
Abstract Objectives We examined the association between long-term bisphosphonates use and morphological change in the femur. Methods 140 patients (97.1% female, 70.8 ± 8.7 years) with over 5-year BP use (8.1 ± 2.4 years) were matched 1:1 for age (± 3), same BMD status with patients as a control group. The primary outcome was femoral lateral bowing (FLB). The hip–knee–shaft angle (HKSA) and femoral neck shaft angle (FNSA) were secondary outcomes. Results Compared with the Control group, the femoral lateral bowing and hip–knee–shaft angle (5.9 ± 4.3° vs. 3.7 ± 1.7°; 6.6 ± 2.6° vs. 5.1 ± 1.5°, respectively) were significantly larger, while the femoral neck shaft angle was significantly lower (128.1 ± 3.4° vs. 129.3 ± 2.5°) in the BP group. The correlation analysis shows there is a positive correlation between the BP therapy time and FLB (r = 0.2566, P < 0.01), HKSA (r = 0.1353, P = 0.1325), while negative correlation between the BP therapy time and FNSA (r = − 0.1637, P = 0.0681) without significance, indicating that the longer BP therapy, the larger the lateral bowing of the femur. Conclusions Patients who took bisphosphonates over 5 years have a larger femoral lateral bowing, hip–knee–shaft angle and a smaller femoral neck shaft angle than control patients.